Infectious biomarkers upon admission predict in-hospital mortality in COVID-19 patients with and without chronic heart failure - Wan, Rong; Tan, Zhaochong; Huang, Ying (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundCoronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), can affect nearly every organ system in the human body and present with diverse clinical manifestations. However, its effects on cardiovascular outcomes remain discrepant.AimThe objective of this study was to determine whether blood inflammatory levels on admission were associated with in-hospital mortality risk in patients with congestive heart failure (CHF) and COVID-19.MethodsWe performed a retrospective analysis of 4,711 inpatients with confirmed SARS-CoV-2 infection from the Dryad database. Among these individuals, 541 CHF patients with COVID-19 were compared with hospitalized non-CHF patients (n = 4,170). Admission variables including demographic characteristics, vital signs, preexisting comorbidities, and laboratory indicators were obtained as potential confounders for in-hospital mortality risk.ResultsUnivariate analysis with Kaplan–Meier curves suggested that higher inflammatory levels on admission—including white blood cell (WBC) count, interleukin-6 (IL-6), ferritin, procalcitonin, and C-reactive protein—were associated with a significantly higher risk of in-hospital mortality compared with lower levels. Consistently, multivariate Cox regression analysis showed that apart from ferritin [0.8 (0.7, 0.9), <0.001], the WBC [1.3 (1.1, 1.5), 0.013], IL-6 [1.4 (1.2, 1.7), <0.001], procalcitonin [1.2 (1.0, 1.3), 0.031] and C-reactive protein [1.2 (1.1, 1.4), 0.002] were independently associated with increased risk of in-hospital mortality in non-CHF patients in the adjusted II model. However, these independent relationships were not observed in CHF patients.ConclusionElevated systemic inflammatory levels on admission were significantly associated with increased in-hospital mortality risk in non-CHF patients with COVID-19 but not in CHF patients. These findings may provide a clinical basis for risk stratification in CHF patients. Further studies are needed to support these results.